A Process of Resection-Dependent Nonhomologous End Joining Involving the Goddess Artemis - Löbrich, Markus (Trends Biochem Sci, 2017)
DNA double-strand breaks (DSBs) are a hazardous form of damage that can potentially cause cell death or genomic rearrangements. In mammalian G1- and G2-phase cells, DSBs are repaired with two-component kinetics. In both phases, a fast process uses canonical nonhomologous end joining (c-NHEJ) to repair the majority of DSBs. In G2, slow repair occurs by homologous recombination. The slow repair process in G1 also involves c-NHEJ proteins but additionally requires the nuclease Artemis and DNA end resection. Here, we consider the nature of slow DSB repair in G1 and evaluate factors determining whether DSBs are repaired with fast or slow kinetics. We consider limitations in our current knowledge and present a speculative model for Artemis-dependent c-NHEJ and the environment underlying its usage.